Critical Appreciation of Power System in Bangladesh - Haque, MA; Azad, J; Rahman, J (Bangladesh Journal of Scientific and Industrial Research, 2010)
The overall civilization of a nation depends on electricity. This is essential for a more stable and livable world, particularly in this age of globalization, information and communication technology. In Bangladesh power system is interconnection of power generation, transmission and distribution. Due to interconnection, the power system becomes large and complex. Shortage of power is a serious problem and strong barrier for the development of our country. Development of power sector indicates the enhancing power generation, reducing system loss and ensures proper distribution among the consumers. In this paper it has been analyzed the main problems and a proposal has been proposed for overcoming those problems that will help to development the power system. Key words: Compact Florescent Lamp (CFL); Independent power producers (IPP); Underground transmission line; Proper load management; Transformers and switchgear; Misuse and corruption and system loss. DOI: 10.3329/bjsir.v45i3.6531 Bangladesh J. Sci. Ind. Res. 45(3), 233-242, 2010